2019
DOI: 10.3389/fneur.2019.01079
|View full text |Cite
|
Sign up to set email alerts
|

First Attack and Clinical Presentation of Hemiplegic Migraine in Pediatric Age: A Multicenter Retrospective Study and Literature Review

Abstract: Background: Data on clinical presentation of Hemiplegic Migraine (HM) are quite limited in the literature, particularly in the pediatric age. The aim of the present study is to describe in detail the phenotypic features at onset and during the first years of disease of sporadic (SHM) and familial (FHM) pediatric hemiplegic migraine and to review the pertinent literature.Results: Retrospective study of a cohort of children and adolescents diagnosed with hemiplegic migraine, recruited from 11 Italian specialized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(62 citation statements)
references
References 13 publications
4
57
1
Order By: Relevance
“…Emotional and intense physical stress, viral infections and head trauma are the more common reported trigger factors for HM attacks. 11 12 Table 1 describes diagnostic criteria for HM, according to the definition of the third edition of International Classification of Headache Disorders. 3…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional and intense physical stress, viral infections and head trauma are the more common reported trigger factors for HM attacks. 11 12 Table 1 describes diagnostic criteria for HM, according to the definition of the third edition of International Classification of Headache Disorders. 3…”
Section: Introductionmentioning
confidence: 99%
“… 20 However, HaNDL is monophasic with resolution in 3 months, while HM recur for decades 62 ; also, only a minority of attacks of HaNDL include visual symptoms, while visual aura is very common in HM. 11 76 …”
Section: Introductionmentioning
confidence: 99%
“…38 39 40 41 42 43 44 45 46 47 48 In fact, in recent years, next-generation sequencing technologies, including exome and mRNA sequencing studies, have been shown to be essential in dissecting the pathophysiology of a wide array of childhood disorders. 49 50 51 52 53 54 55 56 57 58 59 This led to a better understanding of the subcellular alterations underlying diseases, including several regulatory networks and genetic together with nongenetic factors. 60 61 62 63 64 65 66 67 68 69 70 Actually, there is still no effective treatment for JS patients, but our increasing understanding of the underlying genetic basis of various JS-related subtypes and the better genotype–phenotype correlations could lead to an advancement of the field in near future.…”
Section: Discussionmentioning
confidence: 99%
“…In rare cases, diplegia has been reported as a motor aura symptom (18). Compared with FHM, SHM patients tends to have less non-motor auras, longer and more severe attacks, manifesting as acute encephalopathy, characterized by hemiplegia, coma, fever, convulsions, and so on (19). It is thought to be associated with increased glutamic acid release, decreased cortical spreading depression (CSD) threshold, and prolonged and repetitive CSD, all of which lead to cytotoxic and vasogenic edema (17,20).…”
Section: Discussionmentioning
confidence: 99%